Co-gasification of Cassava Rhizome and Woody Biomass in the 1 MWel Prototype Dual Fluidised Bed Gasifier by Gussing Renewable Energy. Issue 1 (April 2020) - Hongrapipat, J; Siriwongrungson, V; Messner, M; Henrich, C.; Gunnarsson, S.; Koch, M.; Dichand, M.; Rauch, R; Pang, S; Hofbauer, H
Abstract: In the current research, the effect of the mixture ratio by weight of wood chips to cassava rhizome (100%:0%, 75%:25%, and 50%:50%) was investigated on the properties of the product gas produced from the Dual Fluidised Bed gasifier power plant. The DFB gasifier power plant is located in Nongbua district, Nakhon Sawan province, Thailand. The results from this study show that the use of 100% wood chips as a fuel generates high quality product gas as designed. The mixture of wood chips and cassava rhizome in the weight ratio of 75%:25% and 50%:50% also gives satisfactory results: steady operation conditions of the whole power plant process, good quality and quantity of product gas, however, the tar content in the product gas was slightly higher than that of using wood chips alone. The researchers found that cassava rhizome can be used as a fuel mixture together with wood chips in the current DFB gasifier at site to generate heat and electricity. The outcome of this research will create the use of waste cassava rhizome, enormously available around the power plant, as well as the broad application of gasification technology using various biomass feedstock types available in Thailand.